Screen time and depression risk: A meta-analysis of cohort studies - Li, Liqing; Zhang, Qi; Zhu, Liyong; Zeng, Guohua; Huang, Hongwei; Zhuge, Jian; Kuang, Xiaorui; Yang, Sule; Yang, Di; Chen, Zhensheng; Gan, Yong; Lu, Zuxun; et al. (Frontiers in Psychiatry, 2022)
Background The impact of screen time on mental health, including depression, has attracted increasing attention from not only children and adolescents but also the elderly. Thus, we conducted a meta-analysis of cohort studies to evaluate the association between screen time and depression risk. Methods The PubMed, Embase, Web of Science, and China National Knowledge Infrastructure databases were searched for cohort studies up to May 2022, and the reference lists of the included studies were also retrieved. A random-effect model was used to estimate the combined effect size. Heterogeneity was assessed with the I2 statistic. Potential publication bias was evaluated using a funnel plot and Begg’s and Egger’s tests. Results The final analysis included 18 cohort studies with a combined total of 241,398 participants. The pooled risk ratio (RR) was 1.10 (95% confidence interval: 1.05–1.14), with significant heterogeneity (I2 = 82.7%, P < 0.001). The results of subgroup analyses showed that the pooled RRs varied according to geographic locations, gender, age group, screen time in the control group, depression at the baseline, and whether the study was conducted during the COVID-19 pandemic. No obvious evidence of publication bias was found. Conclusion This study indicates that screen time is a predictor of depressive symptoms. The effects of screen time on depression risk may vary based on the participant’s age, gender, location, and screen time duration. The findings could have important implications for the prevention of depression.